Impact of omitting clinical target volume in radiotherapy for locally advanced non-small cell lung cancer: a propensity score matching analysis - Liu, Liang; Bao, Wen; Yuan, Xiaoshuai; Zhu, Yaoyao; Zhang, Ying; Christopoulos, Petros; Abbar, Baptiste; Qian, Cheng; Yang, Shuangyan; Xu, Yaping (Translational Lung Cancer Research, 2025)
Background: Determining the planned target volume (PTV) for locally advanced (LA) non-small cell lung cancer (NSCLC) is often a challenging task for radiation oncologists. Due to advances in effective multidisciplinary treatments, the necessity to reconcile the clinical target volume (CTV) with the gross tumor volume (GTV) and the PTV presents an ongoing controversy. This study sought to analyze the effects of omitting the CTV on the clinical outcomes of patients with LA-NSCLC. - Methods: Data were retrospectively collected from all consecutive patients with histologically confirmed LA-NSCLC treated with intensity-modulated radiotherapy (IMRT) at Shanghai Pulmonary Hospital from January 2019 to December 2020. The patients were divided into two groups based on different radiotherapy planning techniques: (I) the planning target volume-gross target (PTV-G) group; and (II) the planning target volume-clinical target (PTV-C) group. The PTV-G was directly based on the GTV, while the PTV-C was based on the simulated CTV. A propensity score matching (PSM) analysis was conducted to enhance the comparability of the clinical data between the two groups. The primary endpoint of the study was the occurrence of radiotherapy-associated adverse events. Secondary endpoints included progression-free survival (PFS), overall survival (OS), post-treatment tumor recurrence patterns, and variations in peripheral blood cell characteristics pre- and post-radiotherapy. - Results: A total of 255 patients were identified from our local database. After matching on propensity score with a 1:2 ratio, 156 patients were included in the final analysis, with 52 in the PTV-G group and 104 in the PTV-C group. The incidence of ≥ grade 3 radiation pneumonitis (RP) was significantly higher in the PTV-C group than in the PTV-G group (12.5% vs. 5.7%, P=0.03). Similarly, the incidence of ≥ grade 3 radiation esophagitis was higher in the PTV-C group than the PTV-G group (15.4% vs. 3.8%, P=0.02). However, no statistically significant differences were found between the PTV-G and PTV-C groups in terms of the objective response rate (ORR) and the disease control rate (DCR) (1-year ORR: 57.7% vs. 55.8%, P=0.37; 1-year DCR: 78.8% vs. 84.6%, P=0.16). No differences were found in median PFS (15.4 months for PTV-G vs. 14.8 months for PTV-C, P=0.28) or median OS (26.8 months for PTV-G vs. 25.4 months for PTV-C, P=0.06). - Conclusions: Omitting the CTV was associated with a decrease of grade ≥3 radiation-induced toxicities without pejorative impact on PFS or OS in LA-NSCLC patients treated with IMRT. Furthermore, no increase in regional or metastatic recurrence rates were observed. This radiotherapy strategy may be a viable option for selected LA-NSCLC patients, reducing toxicities without compromising outcomes.